Dynamic simulation of the soil moisture of apple under drip irrigation with dwarf rootstock in arid saline-alkali areas based on HYDRUS-1D model - Cao, Zhenxi; Zhang, Nan; Huang, Weixiong; Wang, Xingpeng; Gao, Yang (International Journal of Agricultural and Biological Engineering, 2025)
In order to study the soil moisture dynamics and irrigation regimes during the growth period of dwarfing apples in arid and saline-alkali areas, five irrigation treatments (W1: 0.6W3, W2: 0.8W3, W3: 22.5 mm, W4: 1.2W3, W5: 1.4W3) were set up in the southern Xinjiang region. A three-year (2019-2021) field plot experiment of dwarf apple in southern Xinjiang was carried out, and the HYDRUS-1D model was used to simulate the measured data of soil moisture. The root soil moisture transport pattern, root zone soil moisture stress, apple root water absorption capacity, and water deep percolation pattern were analyzed by numerical simulation to evaluate the model’s applicability to actual production in arid saline-alkali areas. Through the simulation analysis of 66 irrigation regimes, it was found that the simulated values of soil moisture content and nitrogen were in good agreement with the measured values, and the values of determination coefficient (R2), root mean square error (RMSE), and consistency index (d) were within a reasonable range. When the sum of soil water stress and deep percolation was between 19.81-21.11 mm, the water loss of farmland reached the minimum. Considering the optimal moisture dynamic analysis in the apple root zone, the recommended irrigation system was 19 times of irrigation, an irrigation quota of 27-36 mm, and an irrigation cycle of 6 d. Through the research results and model simulation, the theoretical basis can be provided for the optimization of irrigation system for dwarf rootstock apple in arid and saline-alkali areas. Keywords: drip irrigated apple, soil moisture dynamics, irrigation regime, numerical simulation DOI: 10.25165/j.ijabe.20251804.9227Citation: Cao Z X, Zhang N, Huang W X, Wang X P, Gao Y. Dynamic simulation of the soil moisture of apple under drip irrigation with dwarf rootstock in arid saline-alkali areas based on HYDRUS-1D model. Int J Agric & Biol Eng, 2025; 18(4): 181–189.